Faktor yang Berhubungan dengan Pemanfaatan Pelayanan Antenatal oleh Ibu Hamil di Wilayah Kerja Puskesmas Tempurejo Kabupaten Jember Tahun 2013 (Correlated Factors of Antenatal Services Utilization by Pregnant Women at Community Health Center of Tempurejo, - Ulul Lailatul Mardiyah; Yennike Tri Herawati; Eri Witcahyo (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Antenatal care is a governmental program as part of efforts to reduce maternal mortality. Indicators of success for prenatal care is K4 scope. Tempurejo Health Center has the lowest coverage of K4 in Jember in 2012 with its percentage is 61.38%, less than the target (94%). The purpose of this study was to analyze correlated factors of antenatal services utilization by pregnant women at Community Health Center of Tempurejo which includes knowledge, attitudes, beliefs, availability of health care, service of 10T, affordability, worker’s service, and family support. This study is a cross sectional analytic design. Samples are 87 pregnant women who stay in the working area Tempurejo Health Center with the age of pregnancy of the 2nd and 3rd trimester. Collecting data using questionnaires and analyzed using correlation Somers'D with Confidence Interval 95%. The results showed correlation between knowledge, attitudes, service of 10T, affordability, worker’s service and family support officer with antenatal services utilization. However, there was no correlation between beliefs and availability of health care with antenatal services utilization. Keywords: pregnant women, antenatal care, utilization